ANALISIS DAMPAK NEGATIF DAN SOLUSI PENYELESAIANNYA TERHADAP KEGIATAN PENAMBANGAN EMAS TANPA IZIN PADA KAWASAN BUKIT NAGA : ANALYSIS OF NEGATIVE IMPACT AND ITS SOLUTIONS ON UNLIMITED GOLD MINING ACTIVITIES IN THE BUKIT NAGA AREA - Saptawartono; Murati, Ferra; Iashania, Yunida; Prayoga, Aditia; Yohanes, Yosindo; Pramana, Andika; Ambeng, Ravie Resido; Silaban, Lamture; Agustina, Lastiur (JURNAL TEKNIK PERTAMBANGAN, 2023)
The Bukit Naga area is an area that has recently attracted the attention of the wider community, because it is alleged to have quite large gold potential.  People flocked to the area to carry out gold mining activities. In order to get an overview of the impacts arising from gold mining activities in the Bukit Naga area, research was carried out on the influence of gold mining activities on the socio-cultural conditions of the community and their environmental conditions, as well as solutions to solving the problems encountered.  The research was conducted using the literature study method for data collection.  Data analysis used descriptive-qualitative method.  The results of the study describe that gold mining activities carried out in the Bukit Naga area have an impact on the socio-cultural conditions of the community (security, health, conflicts of interest in doing business, and local community culture) and environmental conditions (changes in the bio-physical environment, disruption of the ecosystem, reduced and loss of flora and fauna, occurrence of erosion, landslides and floods, as well as environmental pollution). From a legal perspective, the mining activities carried out are illegal activities, which are contrary to and violate the applicable laws and regulations. Problem solving solutions offered: conduct preventive law enforcement, proposing the Bukit Naga area to become a WPR facilitate recommendation and licensing of gold mining business, equipping the community with good and environmentally friendly mining activities and good coordination and collaboration of all parties in managing and utilizing the Bukit Naga gold mining area.  Keywords: Bukit Naga Area, Gunung Mas Regency, Gold Mine